Experiment and calculation of high-temperature effect on tensile performance of GFRP rebars embedded in concrete - Weixue Qian; Chunhua Lu; Siqi Yuan; Hui Li (Case Studies in Construction Materials)
This study examined the degradation of tensile properties of E-glass Fiber Reinforced Polymer (GFRP) rebars embedded in concrete after exposure to elevated temperatures ranging from 100℃ to 800℃. Following thermal treatment, the extracted GFRP rebars underwent the tensile test, providing insights into their thermal resilience. The test results showed that GFRP rebars in 24mm-cover concrete experienced a delayed and nonuniform temperature effect during heating, resulting in a slower appearance change and internal damage to the resin matrix. In comparison to bare GFRP rebars subjected to high temperatures, the heat absorption by the cover concrete allowed the embedded GFRP rebars to retain better tensile properties at temperatures below 400℃. When the temperature exceeded 400℃, the tensile strength of both bare GFRP rebars and GFRP embedded in concrete remained low, with similar degradation levels. Moreover, the degradation mechanisms of GFRP rebars within concrete were analyzed at the microscopic level using scanning electron microscopy (SEM), revealing that the resin matrix exhibited nonuniform degradation following high-temperature exposure. Finally, based on the concrete heat absorption characteristics and thermal degradation mechanism of bare GFRP rebars, a revised model was developed to predict the residual strength of 24mm-concrete covered GFRP rebars after high-temperature exposure. All the above achievements proposed here can advance the understanding of the fire resistance of GFRP rebars in concrete and inform strategies for structural fire protection design.